Non-invasive genetics of the Eurasian lynx of the Western Carpathians - Turbaková, B.; Skrbinšek, T.; Jelenčič, M.; Kutal, M.; Bryja, J. (Josef) (2017)
After the long persecution during the last centuries in Europe, the Eurasian lynx (Lynx lynx) have begun to return slowly to our landscape. In the Czech Republic, in the Moravian-Silesian\nBeskids and Javorníky mountains, there is the edge of the species distribution in the Carpathians. This population is the only autochthonous population of lynx in the Czech Republic and although it is connected with the main source population in the Carpathians, its population size is low and fluctuating. Therefore, it is important to monitor the population and study factors which threaten it the most, i.e. poaching, migration barriers and habitat fragmentation. The main aim of this study was to estimate the population size, density and to analyse the genetic variability and spatial activity of the population using non-invasive genetic method. 156 samples of scat, hair and urine were collected in the study area during snowtracking sessions between 2010–2013. Using in total 19 microsatellite loci and the sex specific marker SRY 18 individuals of lynx were identified. The total population size was estimated at 10–15 individuals, the effective population size at 9,4 individuals. Estimated density was 0,66 individuals per 100 km2 . The number of alleles for each locus was between two and six alleles. The observed heterozygosity was Ho = 0,631 and the expected heterozygosity was He = 0,583. There was no significant deviation from Hardy-Weinberg expectations, therefore the population seems to be large enough for the possible observation of the inbreeding effect. Factorial correspondence analysis indicated that the population is genetically structured, what was confirmed also by significant value of Fst index (Fst = 0,096, P = 0,00167) between geographical subpopulations. This structure is most likely caused by the presence of two „family“ groups – the first one in the Javorníky mountains and the second one in the Moravian-Silesian Beskids.